Purchase Intention in India: A Systematic Review of Branding, Experiential, and Digital Determinants (2009-2026) - Yamburi, Samatha; Prasad, U. Devi (International Review of Management and Marketing, 2026)
In this systematic review, 281 articles on the purchase intention determinants in India were synthesized to investigate the determinants of purchase intention in the country between 2009 and 2026 in Scopus. The analysis shows that the brand image and trust are the main predictors, but such constructs as satisfaction, commitment, and loyalty are underresearched. Experiential issues, such as servicescape, convenience, and perceived value are recognized but hardly ever considered as part of the mainstream branding concepts. The studies of digital purchase intention focus on trust, perceived risk and consumer attitudes, but conceptually disconnected to the offline situations. The literature is highly cross-sectional and structural equation modelling restricting the causal and longitudinal understanding. The results display a disjointed scenery with repetitive model experimentation and brief focus. The research proposes integrative models with bridging branding, experiential and digital determinants and methodological diversification and incorporation of long-term relational effects as loyalty and advocacy. The practical implications are based on the need to establish the brand credibility and transparency, and the need to use the elements of experience to improve the consumer interaction. Future studies have to be extended to rural, MSME, and unorganised retail sectors with longitudinal and mixed methods in order to reinforce the theoretical and practical application. On the whole, this review places purchase intention studies in India as deep in terms of empirical data, but shallow in terms of concept that merits a paradigm shift towards holistic, sustainable, and forward-thinking proposal of consumer-brand relationship systems.